Leg ulcers and hydroxyurea: report of three cases with essential thrombocythemia - (:unkn) unknown (BLACKWELL PUBLISHING LTD, 2002)
Case 1 A 65-year-old woman with essential thrombocythemia (ET) had been taking oral hydroxyurea (HU), 1000 mg daily, for 7 years. Six months ago, she developed an ulcer on the outer part of her left ankle, which healed spontaneously within 2 months. She presented with a new, tender, shallow ulcer, 2 cm x 2 cm in size, at the same site. Doppler examination revealed thrombosis of the left common femoral vein and a calcified atheroma plaque of the left common femoral artery. The dosage of HU was decreased to 500 mg daily when the platelet counts were found to be within normal levels. The ulcer completely healed within 2 months with occlusive wound dressings, and has not recurred within the follow-up period of 1 year. Case 2 A 56-year-old women presented with multiple, painful, leg ulcers of 1 year duration. She had been diagnosed as having ET and had been on HU therapy, 1500 mg/day, for the past 5 years. Interferon-alpha-2b was started 3 months ago, in addition to HU, which was tapered to 1000 mg daily. She had suffered from hypertension for 20 years treated with nifedipine and enalapril, and had recently been diagnosed with diabetes mellitus which was controlled by diet. Examination revealed three ulcers located on the lateral aspects of both ankles and right distal toe. Arterial and venous Doppler examinations were within normal limits. Histopathology of the ulcer revealed nonspecific changes with a mixed inflammatory cell infiltrate around dermal vessels. The ulcers completely healed within 10 weeks with topical hydrocolloid dressings. After healing, she was lost to follow-up. A year later, it was learned that she had developed a new ulcer at her right heel, 3 months after her last visit (by phone call). This ulcer persisted for 8 months until HU was withdrawn. Case 3 A 64-year-old woman with ET presented with a painful leg ulcer of 6 months' duration. She had been taking oral HU for 5 years. She had a 20-year history of hypertension treated with lisinopril. Examination revealed a punched-out ulcer of 2 cm x 2 cm over the right lateral malleolus (Fig. 1). Doppler examination of the veins revealed insufficiency of the right greater saphenous and femoral veins. Angiography showed multiple stenoses of the right popliteal and femoral arteries. As her platelet count remained high, HU was continued. During the follow-up period of 13 months, the ulcer showed only partial improvement with local wound care.
Keywords: DISEASE; THERAPY